Child Migrants and Child Welfare: Toward A Best Interests Approach - Ann Laquer Estin (Washington University Global Studies Law Review, 2018)
Protections for unaccompanied minors in the U.S. immigration system can be traced to our constitutional values of due process and equal treatment; to the parens patriae tradition and best interests principle from family law; and to our commitments under international law including the Protocol to U.N. Convention on the Rights of the Child. With the Trafficking Victims Protection Reauthorization Act of 2008, Congress took an important step toward meeting these obligations and improving our treatment of child migrants, but there is more work to do. Federal agencies have been slow to implement the Act, and there are important gaps in the protections it provides. This paper surveys the current landscape, and argues for a stronger commitment to protecting the welfare of all children within our borders, particularly those who are separated from their parents.
Keywords: Child migrants; Child welfare; best interest; child immigrant; immigration